IMPLEMENTASI PERATURAN GUBERNUR NO.33 TAHUN 2010 TENTANG PENGATURAN TEMPAT DAN PEMBINAAN USAHA MIKRO PEDAGANG KAKI LIMA DI PROVINSI DKI JAKARTA (STUDI PENELITIAN LOKASI BINAAN MERUYA ILIR, JAKARTA BARAT) - Rico Dwi Octavianda; Purwoko .; Nunik Retno Herawati (Journal of Politic and Government Studies, 2015)
One of the policies made by the local government of DKI Jakarta in terms of arrangements place and Guidance Micro Street Vendors stipulated in Governor Regulation No.33 of 2010. This policy is to support micro businesses a solution vendors in Jakarta by providing infrastructure and facilities for micro enterprises vendors on possible locations and temporary which aims to provide legal certainty for the businesses vendors on the site. The initial concept of these policies arise from local government of DKI Jakarta which considers that in order to develop micro-enterprise vendors as services trade which quite large to absorb labor as well as to prevent a negative impact on utilization of city infrastructures, social facilities and other public facilities. Therefore these policies is expected to reduce rate of growth vendors and provide legal certainty to micro businesses vendors and can develop the business sector with the guidance provided.This study aims to analyze implementation the Governor Regulation No. 33 of 2010 concerning Setting and Guidance of Micro Street Vendors by local government of DKI Jakarta in guided location Meruya Ilir, West Jakarta.and see the factors inhibiting and supporting policies that affect the success of implementation the Governor Regulation No. 33 of 2010. As for analyzes using ndicators proposed by George C Edward III. The type of this research is evaluation research policy implementation using qualitative and quantitative approaches. The location of this research is in the location Guided Meruya Ilir, West Jakarta. Technique of information sampling is using purposive sampling and data collecting technique use interview and document analysis.The result of this research shows that Implementation of Governor Regulation No. 33 Year 2010 concerning arrangements place and Guidance of Micro Street Vendors in location Meruya Ilir can be said have not been good enough. This is because the implementation of Governor Regulation No. 33 Year 2010 wasn’t optimal. Implementation driving factors of Governor Regulation No. 33 Year 2010 concerning arrangements place and Guidance of Micro Street Vendors in Guided location meruya ilir among others Implementor Communications, Financial Resources and Dispositions. The factors that become an obstacle in this Governor Regulation are Communication implementor of the target group, Human resources, and bureaucratic structure.The writer recommend are: (1) Increase the number of locations or business area allocated the Guided (2) The location management unit should increase energy human resources in order to achieve a consistent coaching and good supervision function (3) Implementor role should be optimized in their communication and dissemination to the target group these policies.